2001
DOI: 10.1002/1097-0142(20011015)92:8<2084::aid-cncr1549>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of treatment for prostate carcinoma by staging pelvic lymph node dissection and definitive irradiation using low-dose rate temporary iridium-192 interstitial implant and external beam radiotherapy

Abstract: BACKGROUND The objective of this study was to evaluate long‐term treatment outcome of definitive irradiation by using temporary interstitial implant and limited dose of external beam radiotherapy in treatment of localized prostate carcinoma. METHODS In total, 536 patients with biopsy‐proven adenocarcinoma of the prostate, classification T1–T3, underwent staging pelvic lymph node dissection and brachytherapy delivering an average tumor dose of 30 grays (Gy), supplemented by external beam radiation therapy for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
5

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(38 reference statements)
0
8
0
5
Order By: Relevance
“…In the study by Puthawala et al[22] the span is for T3 (45%) to T1 (78%).Tabelle 3. Therapieergebnisse von vier größeren Studien in Bezug aufkrankheitsfreies Überleben (DFS) bzw.…”
unclassified
See 1 more Smart Citation
“…In the study by Puthawala et al[22] the span is for T3 (45%) to T1 (78%).Tabelle 3. Therapieergebnisse von vier größeren Studien in Bezug aufkrankheitsfreies Überleben (DFS) bzw.…”
unclassified
“…Gesamtüberleben (OS) sowie fünf Studien bezüglich der lokalen Kontrolle anhand von Biopsiedaten 4-24 Monate nach Therapie. In der Studie von Puthawala et al[22] wurden T3-Tumoren (45%) bis T1-Tumoren (78%) integriert.…”
unclassified
“…In more contemporary series utilizing biochemical follow-up, the best results 10 report a 5-year biochemical disease-free survival of 77% with radiation alone. A second study utilizing a brachytherapy boost 11 showed a 5-year biochemical failure-free survival rate of 64%. Although the results of these two more recent series seem favorable, the perception of most practitioners, as confirmed by our small group of patients, is that radiation alone is not likely to result in a durable response.…”
Section: Discussionmentioning
confidence: 99%
“…In case of three-dimensional conformal radiation therapy (3D-CRT), if the risk of PLN involvement is ≥ 10%, some advocated PLN dissection prior to radiation therapy [7,9,23]. Laparoscopy is now frequently used for this end, providing better preradiation staging and prognosis.…”
Section: Introductionmentioning
confidence: 99%